Firms Behavior on Contract and Agreement in Small Industry Clusters in Central Java Indonesia. - Sulanjari, Sri; Djajadiningrat, Surna Tjahja (Jurnal Manajemen Teknologi, 2006)
This paper is about firms’ behavior or conduct of small industry clusters. It is a subject matter of industrial economics. Firm conduct is a subject that becomes interesting only when competition is imperfect, or when a few large firms enjoy high market share and are often able to dictate or cooperative in setting price. Small industry is characterized by atomistic market structure. Atomistic market structure has frequently been conjoint with allegedly undesirable market performance attributed to an excessive, destructive, or malfunctioning competition. Many research shows that is real market small industries that established in cluster are not only suistan but also have significant contribution on global trade and economy. This paper is focus on the small firms’ behavior of contract and agreement, furthermore on performance of industry. The finding shows that small firms’ behavior of contract and agreement is a pattern of process based on certain bargaining position. The steps of process of contract and agreement are (1) initiating, (2) managing, and (3) controlling disruption. Fairness is the only variable of supply condition that determines freeness of initiating contract and agreement. While managing contract and agreement and intensity to control disruption on implementing contract and agreement are influenced by variables of demand and supply condition as well as public policy. Industrial environment variables are not directly influence performance of industry, but firms’ behavior of directing and controlling contract and agreement are influencing industrial performance. Keywords:SCP, firms behavior on contract and agreement, small industry cluster